2018
DOI: 10.1080/1351847x.2017.1421245
|View full text |Cite
|
Sign up to set email alerts
|

Is there an Olympic gold medal rush in the stock market?

Abstract: Investor sentiment and attention are often linked to the same non-economic events making it difficult to understand why and how asset prices are affected. We disentangle these two potential drivers of investment behaviour by analysing a new data-set of medals for the major participating countries and sponsor firms over four Summer Olympic Games. Our results show that trading volume and volatility are substantially reduced following Olympic success although returns appear to be largely unaffected. Analysis of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…The stock market was also concluded to be affected by the results of the matches of basketball, hockey, American football, and baseball as concluded by Fan and Wang (2018). Another major sport event at the international level is the Olympic games which affect the volatility and trading volume in the stock market (Wang & Markellos, 2018). Other studies, however, reported no impact for the sport events on the stock market including the study of Devy and Irawan (2019) who concluded that the Asian games did not impact the stock market while Anghel (2018) found that the impact is economically weak.…”
Section: The Impact Of the Sports Matches' Results On Equity Marketsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stock market was also concluded to be affected by the results of the matches of basketball, hockey, American football, and baseball as concluded by Fan and Wang (2018). Another major sport event at the international level is the Olympic games which affect the volatility and trading volume in the stock market (Wang & Markellos, 2018). Other studies, however, reported no impact for the sport events on the stock market including the study of Devy and Irawan (2019) who concluded that the Asian games did not impact the stock market while Anghel (2018) found that the impact is economically weak.…”
Section: The Impact Of the Sports Matches' Results On Equity Marketsmentioning
confidence: 99%
“…For instance, Gao et al (2022) studied the effect of soccer team's results on the stock prices of the firm that owns or sponsor that team using the Chinses stock market although soccer is not the most popular sport in the country (Klingelhöfer, 2022,). Another example is the study of Wang and Markellos (2018) who analyzed the effect of the results of summer Olympic games on the stock markets of many countries including the United States of America and the United Kingdom while most people in the former country prefer to watch American football (Injai, 2022) and most people in the latter country like to watch soccer and cricket matches (Das, 2023). In addition, results of matches used in some of previous studies were analyzed without considering the level of importance of the match as a variable that can affect investors' behavior.…”
Section: The Impact Of the Sports Matches' Results On Equity Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018 and the previous Olympics, for example, for every gold medal won by the United States, S&P 500 companies traded nearly 3% lower the next day. For Germany and South Korea, that decrease was even higher, at 6.7% and 7.3% [1], respectively. And the main reason for the drop in trading volume is those investors, like the entire population, are focused on the Olympics and are distracted by stock market fluctuations, with distractions increasing with sports success.…”
Section: Introductionmentioning
confidence: 89%